2003
DOI: 10.1002/ange.200351545
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Free Synthesis of Rechargeable Solid Oxygen Reservoirs for Clean Hydrogen Oxidation

Abstract: Den Koks loswerden: Das Konzept einer katalytischen oxidativen Dehydrogenierung durch Anwendung fester Sauerstoff‐Austauscher und die lösungsmittelfreie Parallelsynthese eines Satzes von zehn Dimetallkatalysatoren werden beschrieben. Die Verbindungen wurden anhand der selektiven Oxidation von Wasserstoff im Gemisch mit Ethan und Ethylen (KWs) bei 600 °C getestet. Cer‐Wolfram‐Oxid stellte sich als ein ausgezeichnetes stabiles und wiederaufladbares „Sauerstoff‐Reservoir“ heraus (siehe Bild), das 97 % Chemoselekt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…In addition to catalysts 1-18, we also tried preparing Ce 0.9 In 0.1 O 2 (19) (25). However, all of these samples showed secondary phases that were identified as the dopant oxides or dopant metals (see, for example, Figure 1, bottom Scheme 2.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In addition to catalysts 1-18, we also tried preparing Ce 0.9 In 0.1 O 2 (19) (25). However, all of these samples showed secondary phases that were identified as the dopant oxides or dopant metals (see, for example, Figure 1, bottom Scheme 2.…”
Section: Resultsmentioning
confidence: 98%
“…[25] This method enabled the preparation of multiple samples on a 5-10 g scale (Figure 1, left). In a typical synthesis, the metal nitrates (or chlorides or ammonium metallates when nitrates were not available) were co-melted under vacuum, left to boil for four hours, and then calcined at 700 8C, ground, and sieved (70-120 mesh).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, dopant-enriched surface phases can occur for these type of catalysts, and cannot be detected by XRD. [38][39][40] Indeed, in the case of a copper-ceria mixed oxide, Bera et al observed both surface enrichment and bulk incorporation of the copper. [40] .…”
Section: Catalyst Preparation and Characterisationmentioning
confidence: 96%